PERTUMBUHAN SETEK KRISAN (Chrysanthemum sp.) PADA BERBAGAI KONSENTRASI HORMON IBA (Indole Butyric Acid) DI BANGKA DENGAN SISTEM EX-VITRO - Anggri Restikadia; Sitti Nurul Aini; Nyayu Siti Khodijah (Universitas Trilogi, 2021)
Chrysanthemum is an ornamental flower plant that has advantage because of various colors and has long vase time. The minimum potential for chrysanthemum development in Bangka is because of limited seed and the enviroment conditions in Bangka are less than optimal for chrysanthemum plants. The increasing chrysanthemum seedlings can be done vegetatively by addition of IBA hormone with an ex-vitro system. This study aims to determine the effect of IBA (Indole Butyric Acid) hormone on the growth of chrysanthemum cuttings in Bangka. This research was conducted from March to May 2020 at the Research and experimental Garden, Faculty of Agriculture, Fisheries and Biology, Universitas Bangka Belitung. The research method used an experimental method with a single completely randomized design (CRD) consisting of 6 treatments, namely (Control), IBA 50 ppm, IBA 100 ppm, IBA 150 ppm, IBA 200 ppm, IBA 250 ppm. The results showed that giving IBA had no significant effect on the growth of chrysanthemum cuttings in Bangka. Treatment (IBA 150 ppm) tends to be better for the growth of chrysanthemum cuttings in Bangka.